Leg amputation side determines performance in curve sprinting: a case study on a Paralympic medalist - Funken, J.; Heinrich, K.; Willwacher, S.; Müller, R.; Böcker, J.; Hobara, H.; Brüggemann, G. P.; Potthast, W. (Sports Biomechanics, 2019)
The lower limb kinetics of curve sprinting in amputees are not well described in the literature, particularly with respect to the effect of the side of amputation. This is an issue due to the importance of the knowledge for prosthetic design and classification of athletes. Thus, the aim of this study was to investigate the influence of side of amputation on curve sprinting performance in athletes with a unilateral leg amputation. A three-dimensional motion analysis system (Vicon), four force plates (Kistler) and a modified mathematical human model (ALASKA) were used to compare clockwise and counter clockwise curve sprinting lower limb kinematics and kinetics of a Paralympic medalist with a left-sided knee exarticular amputation. Results reveal that vertical ground reaction force application and total vertical impulse were lower when the affected limb was at the inside of the curve. The unaffected limb showed joint mechanics different to those established for non-amputee athletes and might contribute better to propulsion when being the inside limb. Curve sprinting biomechanics and the ability to attain high radial velocities are directly dependent on the side of amputation relative to the curve direction in a unilateral amputee athlete of highest performance level.